Application of Self-Efficacy Theory for Improving Adherence of Older Adult Patients with Glaucoma’s Medication - Abou-El Soud, Faiza A.; PH, Livana (Global Health Science Group, 2024)
Glaucoma is a group of eye conditions that damage the optic nerve, leading to vision loss. Although glaucoma can affect individuals of all ages, the risk of developing the disease rises with age. This article displays the risk factors associated with medication non-adherence and the crucial role of nurses in supporting older adults with glaucoma in their medication adherence journey using self-efficacy theory as a guiding framework. Based on the findings in several studies, it was identified two significant risk factors associated with medication adherence. The first risk factor is patient age, indicating that older patients were more likely to struggle with adherence. This implies that as patients get older, they may face challenges in adhering to their prescribed medication. The second risk factor is the presence of more than three multiple chronic illnesses with poly-medications. This implies that individuals who have multiple chronic illnesses and are taking multiple medications concurrently are at a higher risk of non-adherence to their medication regimen. The complexity and burden of managing multiple conditions and medications may contribute to difficulties in following the prescribed treatment plan. Tailoring the application of self-efficacy theory to the specific needs and preferences of older adults with glaucoma is essential for effective implementation. Conclusion: Nurses as healthcare professionals play a crucial role in supporting older adults with glaucoma in their medication adherence journey using self-efficacy theory as a guiding framework, minimizing the risk of progression, and preventing further vision loss.